On the Utility and Economization of Unretouched Flakes: The Effects of Exterior Platform Angle and Platform Depth. Issue 4 (20th October 2013) - Lin, Sam C.; Rezek, Zeljko; Braun, David; Dibble, Harold L.
Abstract: In recent years, lithic studies have emphasized the role of technology in the overall adaptation of past societies to their environments, including the economization of lithic resources. This paper explores how particular characteristics of individual, unretouched flakes can be altered in ways that increase their economy, as reflected in the ratio of edge length to mass. Results of controlled laboratory experiments are presented that identify exterior platform angle and platform depth as being primary independent variables affecting this ratio. These relationships are then tested against a number of archaeological assemblages.